Mesoporous-microporous hierarchical polyaryletherketone as well as preparation method and application thereof

By using the method of two concentrated sulfuric acid sulfonations and water bath ultrasonic cleaning, a mesoporous-microporous polyaryletherketone was prepared, which solved the problems of insufficient pore structure size and complex modification in the existing technology, and achieved low-cost and efficient cell adhesion and osteogenic differentiation effects.

CN120718322APending Publication Date: 2025-09-30ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510874670.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

The surface pore structure of existing polyaryletherketone materials is small in size, which makes it difficult to meet the needs of cell inward growth. The existing modification methods are cumbersome, complex and costly.

Method used

The mesoporous-microporous polyaryletherketone was prepared by adjusting the sulfonation process twice with concentrated sulfuric acid and combining it with ultrasonic cleaning in a water bath. By adjusting the immersion time and ultrasonic frequency, mesopores of 20-50 μm and micropores of 0.5-5 μm were formed.

Benefits of technology

The pore structure preparation process is simplified, the cost is reduced, and at the same time the cell adhesion and osteogenic differentiation abilities are improved, thereby enhancing bone integration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718322A_ABST
    Figure CN120718322A_ABST
Patent Text Reader

Abstract

The invention discloses a mesoporous-microporous hierarchical polyaryletherketone preparation method, which comprises: 1, soaking a PEEK block in concentrated sulfuric acid, taking out, soaking in deionized water, rinsing, carrying out water bath ultrasonic cleaning, and drying to obtain primary sulfonated PEEK; 2, soaking the PEEK subjected to primary sulfonation in concentrated sulfuric acid again, taking out the PEEK, soaking the PEEK in deionized water for rinsing, performing water bath ultrasonic cleaning, and drying to obtain mesoporous-microporous hierarchical polyaryletherketone; the surface of the mesoporous-microporous hierarchical polyaryletherketone comprises a mesoporous structure with the diameter of 20-50 [mu] m and a microporous structure with the diameter of 0.5-5 [mu] m. According to the method disclosed by the invention, the structure with coexisting mesopores and micropores can be simply prepared on the surface of the PEEK at low cost by virtue of rapid washing after two times of concentrated sulfuric acid treatment soaking. An in-vitro cell experiment result shows that the structure is more beneficial to adhesion and osteogenic differentiation of mouse bone marrow mesenchymal stem cells on the structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a mesoporous-microporous polyaryletherketone and a preparation method and application thereof. Background Art

[0002] Polyetheretherketone (PEEK) is a semicrystalline thermoplastic polymer material with excellent chemical stability, heat resistance, wear resistance, and good biocompatibility. Because its elastic modulus (~3 GPa) is comparable to that of human bone (3-17 GPa), it can effectively reduce bone resorption caused by stress shielding and lower the risk of osteoporosis, and has therefore attracted considerable attention in the field of orthopedic implants.

[0003] However, the PEEK surface is chemically inert and highly hydrophobic, preventing cells from adhering, migrating, proliferating, and differentiating effectively on the surface of the product, necessitating surface modification. Since PEEK is difficult to react with reagents other than concentrated sulfuric acid and methanesulfonic acid at room temperature, sulfonation modification is a common method used to construct a pore structure on the PEEK surface.

[0004] As early as 1985, Bishop et al. (Macromolecules 1985, 18, 86-93.) reported the sulfonation reaction of PEEK with concentrated sulfuric acid. In 2013, Zhao Ying et al. (Biomaterials 34 (2013) 9264-9277.) first focused on the application potential of the structure obtained by sulfonation of PEEK in the biomedical field. However, the pore size obtained by phase separation after a single sulfonation is small, generally around 0.5-5 μm, which does not meet the size of cell ingrowth. Therefore, the sulfonation modification method is often combined with 3D printing, plasma treatment and other methods to construct a multi-level pore structure. The method is cumbersome and complicated, and the cost is high. For example, Chayanun et al. (Materials Today Bio 22 (2023) 100754) used a combination of laser and sulfonation treatment to enhance the biological activity of PEEK. Summary of the Invention

[0005] The present invention addresses the problems that the pore structure of poly(aryletherketone) is small in size, making it difficult to meet the needs of cell ingrowth, and the method of constructing the pore structure is costly and has complicated steps. The invention provides a simple preparation method of mesoporous hierarchical poly(phenylene ether ketone). By adjusting the sulfonation process twice with concentrated sulfuric acid, poly(aryletherketone) having both mesoporous and microporous pore structures is obtained.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a mesoporous-microporous polyaryletherketone comprises the following steps:

[0008] Step 1: immerse the PEEK block in concentrated sulfuric acid, take it out and rinse it in deionized water, then ultrasonically clean it in a water bath and dry it to obtain a sulfonated PEEK;

[0009] Step 2, immersing the PEEK after the primary sulfonation in concentrated sulfuric acid again, taking it out and rinsing it in deionized water, then ultrasonically cleaning it in a water bath and drying it to obtain the polyaryletherketone with the mesoporous-microporous layer;

[0010] The polyaryletherketone surface of the mesoporous-microporous layer comprises a mesoporous structure with a diameter of 20-50 μm and a microporous structure with a diameter of 0.5-5 μm.

[0011] The thickness of the PEEK block is at least 0.2 mm and the volume is at least 20 mm 3 .

[0012] The soaking time in concentrated sulfuric acid in step 1 is 2-5 minutes.

[0013] Soak in concentrated sulfuric acid for 0.5-2 minutes in step 2. The second soaking process should be short to avoid long soaking causing large holes.

[0014] In step 1, the ultrasound is carried out at room temperature, with a power of 100-200 W and a frequency of 30-60 KHz for 5-15 minutes.

[0015] In step 2, the ultrasound is carried out at room temperature, with a power of 100-200 W and a frequency of 30-60 KHz for 5-15 minutes.

[0016] Preferably, the samples are rinsed in deionized water within 10 seconds after being removed from the concentrated sulfuric acid in steps 1 and 2. This is to prevent the acid-washed samples from lingering in the air and absorbing moisture from the air, which can cause slow phase separation on the sample surface and form an uneven surface pore structure.

[0017] The drying in step 1 or step 2 is vacuum drying at 55-75° C. for 2-12 hours.

[0018] Preferably, to ensure that the sample surface is smooth and clean and to reduce the impact of the original microstructure or adhered chemicals on the surface, the sample surface is polished with 500-2000 grit sandpaper, and the sample is washed with one or more of acetone, anhydrous ethanol, and deionized water and dried before use.

[0019] The present invention also provides a mesoporous-microporous poly(aryletherketone) obtained by the aforementioned preparation method. The surface of the mesoporous-microporous poly(aryletherketone) comprises a mesoporous structure with a diameter of 20-50 μm and a microporous structure with a diameter of 0.5-5 μm. The pore walls of the mesoporous structure are composed of a network-like polymer with a diameter of 0.5-1 μm, which directly contributes to the microporous structure. The porosity within a depth of 50 μm from the surface is 50%-80%, and the material at a depth of more than 100 μm from the surface is non-porous, representing an unmodified PEEK matrix.

[0020] The present invention also provides the use of the mesoporous-microporous polyaryletherketone as a biomaterial.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention uses two concentrated sulfuric acid treatments followed by rapid water washing to easily and cost-effectively create a mesoporous and microporous structure on the PEEK surface. In vitro cell experiments show that this structure is more conducive to the adhesion and osteogenic differentiation of mouse bone marrow mesenchymal stem cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are surface and cross-sectional SEM images of the polyaryletherketones of Examples 1-2 of the present invention and Comparative Example 1. Figure 2 These are the CCK-8 cell proliferation test results of Examples 1-2 of the present invention and Comparative Example 1.

[0024] Figure 3 These are the osteogenic gene expression results after co-culturing cells with Examples 1-2 of the present invention and Comparative Example 1.

[0025] Figure 4 These are the alkaline phosphatase staining results after co-culturing cells with Examples 1-2 of the present invention and Comparative Example 1.

[0026] Figure 5 These are the results of Alizarin Red staining after co-culturing cells with Examples 1-2 of the present invention and Comparative Example 1.

[0027] Figure 6 Surface SEM images of polyaryletherketones of comparative examples 2-4 of the present invention.

[0028] Figure 7 This is the SEM image of the surface of the polyaryletherketone of Comparative Examples 5-6 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples and Comparative Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art will make modifications or equivalent replacements based on understanding the technical solution of the present invention, without departing from the spirit and scope of the technical solution of the present invention, and all should be encompassed within the scope of protection of the present invention.

[0030] The raw materials used in the following specific embodiments were purchased from the market. The necessary performance structure characterization and testing methods are as follows:

[0031] CCK-8, short for Cell Counting Kit-8, is a reagent that allows for simple and accurate cell proliferation and toxicity analysis. Its basic principle is that the reagent contains a water-soluble tetrazolium salt, 2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfonatophenyl)-2H-tetrazolium monosodium salt (WST-8), which is reduced by cellular dehydrogenases to a highly water-soluble yellow formazan dye under the action of the electron carrier 1-methoxy-5-methylphenazinium dimethyl sulfate (1-Methoxy PMS). The amount of formazan generated is proportional to the number of viable cells, allowing direct analysis of cell proliferation and toxicity.

[0032] PCR, short for polymerase chain reaction, is a molecular biology technique used to amplify specific DNA fragments in vitro. Quantitative real-time PCR (qPCR) involves adding fluorescent dyes or groups to the PCR amplification reaction system. Fluorescent signals are collected throughout the PCR process to monitor the amount of amplified product in real time during each cycle. Finally, a standard curve and CT values ​​are used to quantitatively analyze the sample under test.

[0033] Alkaline phosphatase (ALP), also known as alkaline phosphatase, catalyzes the hydrolysis of phosphate bonds under alkaline conditions and is a hallmark enzyme of mature osteoblasts. The basic principle of ALP staining is that intracellular ALP hydrolyzes naphthol phosphate AS-MX at pH 9.4-9.6 to produce naphthol, which is then captured by a diazonium salt, forming an insoluble colored precipitate.

[0034] Alizarin Red S (ARS) staining is a commonly used staining method, widely used in studies of osteoblast differentiation, bone cells, and tissue pathophysiology. An anthraquinone derivative, ARS chelates with various metal ions to form stable orange-red or deep-red complexes. It is an excellent metal indicator and can also be used as a colorimetric reagent for the determination of metal ions by absorbance, as an acid-base indicator, or for polarographic determination of metal ions. In histology and histopathology, ARS is often used to stain or locate calcium deposits in tissues because it chelates with calcium salts in calcium carbonate or calcium phosphate to form an orange-red complex.

[0035] Example 1

[0036] The following steps were followed to prepare polyaryletherketone with a mesoporous-microporous surface structure:

[0037] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. To ensure a smooth and clean surface and minimize the effects of the original surface microstructure or adhering chemicals, the sample surface was polished using 500-, 1000-, and 2500-grit metallographic sandpaper, respectively. The sample was then washed with acetone, anhydrous ethanol, and deionized water, and finally dried in a vacuum oven at 60°C and -0.1 MPa for 2 hours.

[0038] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0039] Step 2: After removing the sulfuric acid, the sample obtained in step 1 was quickly (within 5 seconds) immersed in deionized water for rinsing. After the sample color no longer changed, the water bath was changed and ultrasonic cleaning was performed. The ultrasonic temperature was 25°C, the ultrasonic power was 120W, the ultrasonic frequency was 40kHz, and the ultrasonic time was 10 minutes. The thoroughly cleaned sample was placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours.

[0040] Step 3: Under magnetic stirring, the sample obtained in step 2 is immersed in 98% concentrated sulfuric acid again to sulfonate the surface of the sample where the porous structure has been formed. The sulfonation time is 2 minutes.

[0041] Step 4: Immerse the sample obtained in step 3 in deionized water for rinsing. After the sample color no longer changes, replace the water bath and perform ultrasonic cleaning. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours to obtain a secondary sulfonated sample (S2PEEK).

[0042] Example 2

[0043] The following steps are used to prepare polyaryletherketone with a porous surface:

[0044] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0045] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0046] Step 2: After removing the sulfuric acid, the sample obtained in step 1 was quickly (within 5 seconds) immersed in deionized water for rinsing. After the sample color no longer changed, the water bath was replaced and ultrasonic cleaning was performed. The ultrasonic temperature was 25°C, the ultrasonic power was 120W, the ultrasonic frequency was 40kHz, and the ultrasonic time was 10 minutes. The thoroughly cleaned sample was placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours to obtain a once sulfonated sample (SPEEK).

[0047] Comparative Example 1

[0048] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, it was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h to obtain an unmodified PEEK sample.

[0049] Comparative Example 2

[0050] The following steps are used to prepare polyaryletherketone with a porous surface:

[0051] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0052] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0053] Step 2: After removing the sulfuric acid from the sample obtained in step 1, place it in air for 15 minutes, then rinse it in deionized water. After the sample color no longer changes, replace the water bath and ultrasonically clean it. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours.

[0054] Comparative Example 3

[0055] The following steps are used to prepare polyaryletherketone with a porous surface:

[0056] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0057] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0058] Step 2: After removing the sulfuric acid, the sample obtained in step 1 is quickly immersed in deionized water for rinsing, but the water bath is not changed for ultrasonic cleaning. The sample is placed in a vacuum drying oven at 60° C. and -0.1 MPa for 2 h.

[0059] Comparative Example 4

[0060] The following steps were followed to prepare polyaryletherketone with a mesoporous-microporous surface structure:

[0061] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0062] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0063] Step 2: Within 3 seconds of removing the sulfuric acid, completely immerse the sample obtained in step 1 in deionized water for rinsing. After the sample color no longer changes, replace the water bath and ultrasonically clean it. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours.

[0064] Step 3: Under magnetic stirring, the sample obtained in step 2 is immersed in 98% concentrated sulfuric acid again to sulfonate the surface of the sample where the porous structure has been formed. The sulfonation time is 10 minutes.

[0065] Step 4: Immerse the sample obtained in step 3 in deionized water for rinsing. After the sample color no longer changes, replace the water bath and perform ultrasonic cleaning. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours to obtain a secondary sulfonated sample (S2PEEK).

[0066] Comparative Example 5

[0067] The following steps were followed to prepare polyaryletherketone with a mesoporous-microporous surface structure:

[0068] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0069] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0070] Step 2: Within 3 seconds of removing the sulfuric acid, completely immerse the sample obtained in step 1 in 1,3-dimethyl-2-imidazolidinone (DMI) for rinsing. After the sample color no longer changes (approximately 30 minutes), immerse it in deionized water and ultrasonically clean it. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours.

[0071] Comparative Example 6

[0072] The following steps were followed to prepare polyaryletherketone with a mesoporous-microporous surface structure:

[0073] The sample was a PEEK disc with a diameter of 34 mm and a thickness of 0.3 mm. The sample surface was polished with 500 mesh, 1000 mesh, and 2500 mesh metallographic sandpaper in sequence, and the sample was washed with acetone, anhydrous ethanol, and deionized water. Finally, the sample was vacuum dried in a vacuum drying oven at 60°C and -0.1 MPa for 2 h.

[0074] Step 1: Under magnetic stirring, immerse the disc-shaped PEEK sample in 98% concentrated sulfuric acid to sulfonate its surface for 5 minutes.

[0075] Step 2: Within 3 seconds of removing the sulfuric acid, completely immerse the sample obtained in step 1 in N,N-dimethylpropylene urea (DMPU) for rinsing. After the sample color no longer changes (approximately 2 hours), immerse it in deionized water and ultrasonically clean it. The ultrasonic temperature is 25°C, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and the ultrasonic time is 10 minutes. The thoroughly cleaned sample is placed in a vacuum drying oven at 60°C and -0.1MPa for 2 hours.

[0076] Figure 1 The following are surface and cross-sectional SEM images of the samples obtained in Examples 1-2 and Comparative Example 1. As can be seen from the surface SEM images, the unmodified PEEK surface is smooth and flat, which is not conducive to integration with cell tissues after implantation and has poor osteointegration. The SPEEK surface in Example 2 has a 0.5-5 μm bicontinuous pore structure, which is more conducive to cell adhesion but still does not meet the conditions for cell ingrowth. The S2PEEK surface in Example 1 has both a 20-50 μm mesoporous structure and a 0.5-5 μm microporous structure, which is more conducive to cell adhesion while also meeting the conditions for cell ingrowth and has better osteoconductivity.

[0077] It can be seen from the cross-sectional SEM image that there is no pore structure on the surface of the unmodified PEEK in Comparative Example 1, and cells cannot grow inward; in Example 2, there is a pore structure of about 10 μm in the deeper layer of the SPEEK surface, but since the top layer is a microporous structure with a smaller pore size, it is not conducive to the ingrowth of cells; while the pore structure of S2PEEK in Example 1 presents 20-50 μm mesopores distributed on the surface of the sample, and some of them are interconnected, which is conducive to the ingrowth of cells.

[0078] Figure 2 The results of the CCK-8 cell proliferation test of mouse bone marrow mesenchymal stem cells (BMSCs) co-cultured on the sample surfaces obtained in Examples 1-2 of the present invention and Comparative Example 1. After the materials were co-cultured with the cells for 1 day, 3 days, and 7 days, the culture medium was aspirated and 1 ml of complete culture medium containing 10% CCK-8 was added, and the cells were incubated at 37 ° C for 4 hours. 200 μL of supernatant was taken from each well into a 96-well plate, and the absorbance was measured at 450 nm using a microplate reader. The results showed that the cells in the modified SPEEK and S2PEEK groups proliferated normally with increasing culture time, but were slightly lower than those in the PEEK group. The sulfonic acid group introduced after the modification may cause the pH of the culture medium to change, but its toxicity to the cells is low, and the cells can still grow normally.

[0079] Figure 3The results of osteogenic gene expression in BMSCs co-cultured on the surfaces of the samples obtained in Examples 1-2 and Comparative Example 1 of the present invention are shown. After 7 days of co-culture of the materials with the cells, q-PCR was used to analyze the expression of type I collagen (Col1A1), osteopontin (OPN), and Runt-related transcription factor 2 (Runx2) in the BMSCs cells. The results showed that compared to unmodified PEEK, cells cultured on SPEEK showed significantly upregulated expression of the Col1A1 gene, while cells cultured on S2PEEK showed higher expression levels of both OPN and Runx2 genes, indicating that S2PEEK has a better ability to promote osteogenic differentiation. RQ is the relative quantitative value of the gene.

[0080] Figure 4 The following are the results of ALP staining of BMSCs co-cultured on the surfaces of the samples obtained in Examples 1-2 and Comparative Example 1. After 7 days of co-culture with the cells, the culture medium was aspirated and washed once with PBS buffer. The samples were fixed with tissue fixative for 30 minutes and washed again three times with PBS buffer. The samples were then stained with an alkaline phosphatase detection kit for 30 minutes in the dark. After staining, the samples were thoroughly rinsed with distilled water and photographed using a scanning microscope. The results show that cells cultured on S2PEEK maintained good activity regardless of whether they were cultured with culture medium containing osteogenic induction solution or standard culture medium.

[0081] Figure 5 The results of ARS staining of BMSCs co-cultured on the surfaces of the samples obtained in Examples 1-2 and Comparative Example 1 are shown. After 7 days of co-culture, the culture medium was aspirated and the cells were washed once with PBS buffer. The cells were fixed with a tissue fixative for 30 minutes, washed again with PBS buffer three times, and then stained with ARS staining reagent for 30 minutes. After staining, the cells were thoroughly rinsed with distilled water and photographed using a scanning microscope. The results showed that cells cultured on S2PEEK using a culture medium containing an osteogenic induction solution had more calcium nodules deposited, indicating that S2PEEK has a better mineralization effect than PEEK.

[0082] Figure 6 The SEM images of the sample surfaces obtained in Comparative Examples 2-4 of the present invention. In Comparative Example 2, when the sample was not quickly immersed in water after sulfonation, but exposed to the air for a period of time, the concentrated sulfuric acid carried on the surface of the sample would absorb moisture in the air, causing a slow phase separation on the surface of the sample, forming an uneven surface pore structure. In Comparative Example 3, when the sample was dried without ultrasonic cleaning after treatment, the sulfuric acid remaining in the pore structure was concentrated to form concentrated sulfuric acid during the drying process, which would change the structure of the sample surface again. It manifests as yellowing of the surface of the sample after drying, the disappearance of the microporous structure, the acidic surface, and greater cytotoxicity. In Comparative Example 4, when the second sulfonation time of the sample was 10 minutes, the obtained mesopore depth was shallow, and the binding strength with the cell tissue was reduced.

[0083] Figure 7 The following are SEM images of the sample surfaces obtained in Comparative Examples 5-6 of the present invention. When the sample is immersed in a solvent other than water after sulfonation, the pore structure formed on the sample surface is affected by the properties of the solvent. DMI and DMPU, as organic solvents, have poor compatibility with sulfuric acid, which is manifested as a decrease in the rate of liquid-liquid exchange (as can be seen from the prolonged color change time of the sample). The slower phase separation rate results in the formation of a microporous structure composed of a network polymer structure on the sample surface. Instead, a pore structure with a diameter of 1-5 μm that is not interconnected is formed. At the same time, fewer macroporous structures are observed inside the sample immersed in DMPU, indicating that the macroporous structure is related to the faster phase separation rate.

[0084] It can be seen that the process of washing with water after concentrated sulfuric acid treatment is the step of generating micropores and mesopores. The surface of PEEK in concentrated sulfuric acid is gel-like. If it is not washed with water (for example, by using other reagents), different phase separation processes may occur, leading to different results (currently, the results obtained by immersing DMI, DMPU and other solutions in concentrated sulfuric acid have been obtained, such as Comparative Examples 5 and 6);

[0085] Ultrasonic treatment is used to strengthen the cleaning of residual acid in the pores. If ultrasonic cleaning is reduced, although the structure will not be affected, the residual acid will cause cytotoxicity and cannot be used for cell culture. In addition, the residual sulfuric acid may return to the state of concentrated sulfuric acid due to the continuous evaporation of water when dried at a higher temperature (such as 80°C), causing structural changes on the sample surface.

[0086] The present invention constructs a polyaryletherketone (PEEK) material with both 20-50μm mesopores and 0.5-5μm micropores on the surface of PEEK through two sulfonation steps. This modification method is simple, low-cost, and maintains the original mechanical properties of the PEEK inside the product. When implanted in the body, this surface-modified polyaryletherketone material facilitates the adhesion and growth of osteoblasts, promotes rapid bone ingrowth, forms a good bond, and significantly enhances the osseointegration of the implant.

Claims

1. A method for preparing a mesoporous-microporous polyaryletherketone, characterized in that: The steps include: Step 1: immerse the PEEK sample in concentrated sulfuric acid, take it out and rinse it in deionized water, then ultrasonically clean it in a water bath and dry it to obtain a sulfonated PEEK; Step 2, immersing the PEEK after the primary sulfonation in concentrated sulfuric acid again, taking it out and rinsing it in deionized water, then ultrasonically cleaning it in a water bath and drying it to obtain the polyaryletherketone with the mesoporous-microporous layer; The polyaryletherketone surface of the mesoporous-microporous layer comprises a mesoporous structure with a diameter of 20-50 μm and a microporous structure with a diameter of 0.5-5 μm.

2. The method for preparing a mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: The thickness of the PEEK sample is at least 0.2 mm and the volume is at least 20 mm 3 .

3. The method for preparing a mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: The soaking time in concentrated sulfuric acid in step 1 is 2-5 minutes.

4. The method for preparing mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: In steps 1 and 2, all samples were immersed in deionized water within 10 seconds after being taken out of concentrated sulfuric acid.

5. The method for preparing mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: Soak in concentrated sulfuric acid in step 2 for 0.5-2 minutes.

6. The method for preparing mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: In step 1, the ultrasound is carried out at room temperature, with a power of 100-200 W and a frequency of 30-60 KHz for 5-15 minutes.

7. The method for preparing mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: In step 2, the ultrasound is carried out at room temperature, with a power of 100-200 W and a frequency of 30-60 KHz for 5-15 minutes.

8. The method for preparing mesoporous-microporous polyaryletherketone according to claim 1, characterized in that: The drying in step 1 or step 2 is vacuum drying at 55-75° C. for 2-12 hours.

9. The mesoporous-microporous polyaryletherketone prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The mesoporous-microporous polyaryletherketone surface includes a mesoporous structure with a diameter of 20-50 μm and a microporous structure with a diameter of 0.5-5 μm; the porosity of the material within a depth of 50 μm from the surface is 50%-80%, and the material with a depth of more than 100 μm from the surface is non-porous.

10. Use of the mesoporous-microporous polyaryletherketone according to claim 9 as a biomaterial.